2014
DOI: 10.1080/19393210.2014.967814
|View full text |Cite
|
Sign up to set email alerts
|

Patulin and its dietary intake by fruit juice consumption in Iran

Abstract: A survey was conducted to determine levels and dietary intake of patulin (PAT) from fruit juices consumed in Iran. PAT content was determined using high performance liquid chromatography-diode array detection in 161 samples of fruit juices including apple, pineapple, pear, peach, pomegranate and white and red grape juices. Results revealed the presence of PAT in 16.1% of the samples examined, ranging from 5 to 190.7 µg/kg. Average and median PAT content in positive samples was 34.5 and 18.5 µg/kg, respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 24 publications
0
9
2
Order By: Relevance
“…The maximum dietary intake level was 1.93 µg/kg bw/day of sweet orange in Sawt city. Rahimi and Jeiran [36] estimated the daily intake of PAT from fruit juice at 16.4, 45.9, and 74.6 ng/kg bw/day in Iranian adults, children, and babies, respectively, two orders of magnitude lower than the levels estimated in the present research. Relatively low values of PAT daily intake were estimated in a previous study by our group, analyzing the effect of consumption of fruit, juices and smoothies [22].…”
Section: Daily Intake Assessment Of Patulincontrasting
confidence: 72%
“…The maximum dietary intake level was 1.93 µg/kg bw/day of sweet orange in Sawt city. Rahimi and Jeiran [36] estimated the daily intake of PAT from fruit juice at 16.4, 45.9, and 74.6 ng/kg bw/day in Iranian adults, children, and babies, respectively, two orders of magnitude lower than the levels estimated in the present research. Relatively low values of PAT daily intake were estimated in a previous study by our group, analyzing the effect of consumption of fruit, juices and smoothies [22].…”
Section: Daily Intake Assessment Of Patulincontrasting
confidence: 72%
“…Rahimi and Rezapoor (2015) conducted a survey to determine patulin level in 161 samples of fruit juices, including apple, pineapple, pear, peach, pomegranate, as well as white and red grape juices. In the mentioned study, 16.1% of the samples were contaminated (range: 5-190.7 µg/kg), and 2.5% of the apple juice samples were contaminated at concentration higher than 50 µg/L [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…In Malaysia, Lee et al [4] found to be PAT positive 5% of 56 analyzed fruit juices in a range of concentration between 13.1 and 33.7 µg/L. In Iran, Rahimi et al [19] revealed also PAT presence in 16% of 161 fruit juices samples with levels between 5 to 190.7 µg/kg and mean of positives of 34.5 µg/kg. Contrary to the present study, in Tunisia, Zouaoui et al [20] reported PAT incidence of 50% in 214 samples of fruit juices, compote and jam samples and concentrations ranging from 2 to 889 µg/L and a mean of 89 µg/L.…”
Section: Mycotoxin Contents In Juicesmentioning
confidence: 99%